# Thread: BODMAS AND SIMPLIFYING AN EXPRESSION

1. ## BODMAS AND SIMPLIFYING AN EXPRESSION

Here is my current matter at hand. The problem below ask me to simplify it and I have no real background with using the B of BODMAS method so I would like you to check out what I have and maybe offer some assistance if you will. Here we go.

5[3(2x-2)+3]
=3(x)+3
=6x(5)
=11x

Now this is what I have and I was wondering if I could please get some feedback and direction from someone.
Thanks,
watcjpp

2. 5[3(2x-2)+3]

the 2x-2 cannot be made to equal x

3(2x-2)= 6x -6

then use this back in your equation

5( (6x-6) +3)

= 5( 6x-3)
=30x -15

3. Thanks because I could not find anything that was even close to explaining these operations. I was really thrown off by the Bracket and well I was trying to figure it out.

Again Thanks.

so here we go
5[3(2x-2)3]
3(2x-2)=6x-6
5((6x-6)+3)
=5(6x-3)
=30x-15
Again thanks for the direction once again my headache has been lessened and I learned something new.

#### Posting Permissions

• You may not post new threads
• You may not post replies
• You may not post attachments
• You may not edit your posts
•